573 Postural Analysis in Patients with Parkinson's Disease and the Importance of Physical Exercise for Postural Correction (Balneo and PRM Research Journal, 2024)
Abstract: In the case of Parkinson disease, the postural abnormalities accentuate as the disease advances. The loss of the gravity center is determined by the deviations from the normal posture like the changing of the head position, the anterior bending of the trunk and semi flexions of the superior and inferior members. The aim of this study is to identify the modifications of the posture and of the alignment of the body in the case of the Parkinson disease patients, following the physical exercise program.Within the study, forty patients with Parkinson disease were analyzed using Softului GaitON Posture Analysis. Following the postural analyses, the patients were integrated into a physical exercise program, for six months.The results of the study indicate significant positive changes concerning the realignment of the head posture, p=0.02, of the shoulders p=0.02, anterior superior iliac crest. Through the postural analyses system, we monitored the evolution and the efficacy of the rehabilitation program, in its dynamic.The  GaitON Posture Analysis  system proved to be  a good indicator for the evaluation and the monitoring of the patients with Parkinson disease. The physical exercise program, which was recommended to the patients, demonstrated to be effective and an important tool for the improvement of the posture.